(untitled) (Scientific journal of the Fergana State University, 2024)
One of the important requirements defined in the program of the primary grade mother tongue and reading literacy textbook is to develop students’ speech. Because the level of students’ speech, their reading skills, their opinions, and their imagination are related to speech. That’s why we found it preferable to use the means of folk oral creativity to improve students’ speech. Proverbs, riddles, fairy tales, quick sayings and parables are the main tools for improving oral speech of elementary school students. Fundamental reforms in the field of education have been implemented in our country in recent years and many achievements are being made. It should be said that the content and structure of the updated textbooks and the re-creation of educational tools serve to improve the knowledge of the students as well as their speaking skills. In particular, the provision of theoretical, artistic, formal, descriptive and discussion texts in native language textbooks increases the quality and effectiveness of education. From this point of view, first of all, it is important to understand the scientific basis of the text. "In the course of speech, sentences are grouped, thematically united according to their structure and tone, and form a separate syntactic unit - a complex syntactic whole. However, not all sentences in the text are part of a complex syntactic whole, some of them are not its components. Consequently, the speech of the speaker in the process of speech consists of short short texts. Surroundings and different opinions may not correspond to the content of the text.